Risk reduction through Europe's distressed debt market - Alexander Lehmann (Bruegel, 2018)
The market for distressed debt will need to play a more prominent role in Europe's emerging strategy to tackle the legacy of non-performing loans (NPLs). This market could speed up NPL resolution and allow greater flexibility in bank balance sheet management. Investors could contribute crucial skills and possibly capital to the process of workout and restructuring. The loan sale process potentially suffers from a number of market imperfections which manifest themselves in high valuation gaps, and in the market failing to cover certain asset types. In Europe, turnover from distressed debt sales remains limited relative to the total stock of exteuro870 billion in non-performing loans, and the additional stock of exteuro1.1 trillion of so-called non-core banking assets, which banks also seek to divest in this market. There has so far been little market demand for the bulk of unsecured assets among small and medium-sized companies and other corporate borrowers, loans held by smaller banks with their higher NPL ratios, or exposures to larger enterprises that could benefit from comprehensive debt restructuring and additional finance. Significant further supply might now come into the market as stricter supervisory guidelines are implemented, and as new accounting guidelines force higher provisioning levels. Improved national restructuring and insolvency regimes are beginning to attract a wider range of investors. An initiative by EU finance ministers to improve transparency around loan quality and foster greater liquidity through transaction platforms might lower transaction-specific fixed costs somewhat. More decisive public support, for instance through asset management companies or in securitisation structures, might be needed. As a significant share of Europe's banking assets might move into the hands of little-known investors, some of the benefits of relationship banking could be lost, and the conduct of the loan servicers will come into the focus of regulators.
Keywords: 330